Millimeter wave low-loss LTCC dielectric material and preparation method thereof

Through the raw materials and process processing of specific ratios, low-loss LTCC dielectric materials with dielectric constants of 5.6 to 6.0 and dielectric loss of (1 to 40GHz) < 0.002 were prepared, which solved the problem of high dielectric loss of the millimeter wave band LTCC dielectric materials in the prior art, and achieved excellent dielectric performance and high matching.

CN119661073APending Publication Date: 2025-03-21SUZHOU R&D CENT OF NO 214 RES INST OF CHINA NORTH IND GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411965021.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, LTCC dielectric materials in millimeter wave bands have high dielectric losses in high frequency bands, which is difficult to meet the demand for low loss.

Method used

LTCC dielectric materials made of ethanol, methyl ethyl ketone, glass powder and binder were prepared by using specific raw material ratios and process processing to prepare low-loss LTCC dielectric materials with dielectric constants of 5.6 to 6.0 and dielectric loss of (1 to 40GHz) < 0.002.

Benefits of technology

It realizes LTCC dielectric materials with excellent dielectric properties in the millimeter wave frequency band, with low loss and high matching, and can match with commercially used LTCC electronic pastes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661073A_ABST
    Figure CN119661073A_ABST
Patent Text Reader

Abstract

The invention discloses a millimeter wave low-loss LTCC (Low Temperature Co-Fired Ceramic) dielectric material and a preparation method thereof in the technical field of functional materials. The millimeter wave low-loss LTCC dielectric material is prepared from the following raw materials in parts by mass: 7-9 parts of ethanol, 11-13 parts of methyl ethyl ketone, 38-42 parts of glass powder and 9-11 parts of a binder. The shrinkage rates of the millimeter wave low-loss LTCC dielectric material in the X and Y directions are 15 + / -0.3%, the millimeter wave low-loss LTCC dielectric material can be matched with commercial high-frequency LTCC electronic paste, the dielectric constant is 5.6-6.0, the dielectric loss (1-40 GHz) is less than 0.002, and the millimeter wave low-loss LTCC dielectric material has excellent dielectric properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a millimeter wave low-loss LTCC dielectric material and a preparation method thereof. Background Art

[0002] LTCC dielectric material (i.e., green ceramic tape) is the key basic material for manufacturing LTCC devices or components. For example, LTCC green ceramic tape and its supporting thick-film electronic paste are used to make LTCC substrates, and an integrated packaging shell is made on the substrate. Micro-inertial device chips (micro-gyroscopes and micro-accelerometers), signal processing ASIC (Application Specific Integrated Circuit) chips and other components are precisely assembled and finally hermetically sealed to form an LTCC integrated device, realizing integrated processing functions such as guidance and control solution, navigation solution, and satellite positioning solution.

[0003] The most commonly used LTCC dielectric materials in the current research and production of electronic components are DuPont 951 and Ferro A6 LTCC raw ceramic materials. The former is used for high strength and high density, and the latter is used for high frequency bands. DuPont 951 series LTCC raw ceramic tape belongs to the "glass + ceramic" material, which has the advantages of excellent performance, stable quality, and wide application process window. It has always been the most commonly used LTCC raw ceramic tape for the research and production of high-strength, high-density, and high-performance integrated LTCC components in China. Ferro A6 type LTCC raw ceramic tape belongs to the "microcrystalline glass" system, which has the advantages of low dielectric and low loss. It has always been the most commonly used LTCC raw ceramic tape for the research and production of LTCC modules such as millimeter-wave frequency phased array TR components and missile-borne RF front ends. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a millimeter wave low-loss LTCC dielectric material and a preparation method thereof. The LTCC dielectric material can match the LTCC electronic paste used in commercial high frequency, has a dielectric constant of 5.6 to 6.0, a dielectric loss of (1 to 40 GHz) < 0.002, and has excellent dielectric properties.

[0005] To achieve the above object, the present invention is implemented by adopting the following technical solutions:

[0006] On the one hand, the present invention provides a millimeter wave low-loss LTCC dielectric material, which is prepared from the following raw materials in parts by weight: 7-9 parts of ethanol, 11-13 parts of methyl ethyl ketone, 38-42 parts of glass powder and 9-11 parts of a binder;

[0007] Wherein, the glass powder is composed of 15-16 parts by mass of a first melting point glass powder and 3-5 parts by mass of a second melting point glass powder, and the first melting point glass powder is doped with La2O3 and Nd2O3;

[0008] The first melting point is 1490-1510°C; the second melting point is 1390-1410°C.

[0009] Furthermore, the glass powder is composed of 15-16 parts by mass of first melting point glass powder and 3-5 parts by mass of second melting point glass powder.

[0010] Furthermore, the first melting point glass powder is prepared from the following raw materials in parts by mass: 35-45 parts of CaO, 15-20 parts of B2O3, 36-46 parts of SiO2, 0.1-1 parts of K2O, 1-2 parts of Na2O, 0.1-1 parts of La2O3 and 0.1-2 parts of Nd2O3.

[0011] Furthermore, the second melting point glass powder is prepared from the following raw materials in parts by mass: 35-45 parts of CaO, 33-43 parts of SiO2 and 16-26 parts of B2O3.

[0012] Furthermore, the particle size of the glass powder is 1.8-2.2 μm.

[0013] On the other hand, the present invention provides a method for preparing the millimeter wave low-loss LTCC dielectric material, comprising:

[0014] Obtaining raw materials of a first melting point glass powder and a second melting point glass powder according to weight, and subjecting them to ball milling, drying, melting and water quenching treatments in sequence to obtain a water-quenched material;

[0015] The water-quenched material is ball-milled, sieved and dried to obtain glass powder;

[0016] Obtain the glass powder, ethanol, methyl ethyl ketone and binder according to weight parts, mix the above materials evenly, and prepare slurry;

[0017] The slurry is subjected to tape casting treatment and dried under multiple temperature conditions to prepare a millimeter wave low-loss LTCC dielectric material.

[0018] Furthermore, the ball milling time is 2-4 hours and the rotation speed is 100-200 rpm.

[0019] Furthermore, the melting temperature is 1300-1500° C., and the melting time is 1-2 hours.

[0020] Furthermore, the mesh size of the sieving is 600 meshes.

[0021] Furthermore, the equipment for the casting process adopts a casting machine, and the casting speed is 1.0-1.2 m / min;

[0022] And / or, the drying under multiple temperature conditions is specifically drying under three temperature zones of the casting machine, wherein the drying temperature of the first temperature zone is 42-48°C, the drying temperature of the second temperature zone is 52-58°C, and the drying temperature of the third temperature zone is 62-68°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention provides a millimeter wave low-loss LTCC dielectric material and a preparation method thereof. The millimeter wave low-loss LTCC dielectric material is prepared from the following raw materials in parts by mass: 7-9 parts of ethanol, 11-13 parts of methyl ethyl ketone, 38-42 parts of glass powder and 9-11 parts of a binder. The prepared LTCC dielectric material has a shrinkage rate of 15±0.3% in the X and Y directions, which can match the LTCC electronic paste used in commercial high-frequency applications.

[0025] The present invention provides a millimeter wave low-loss LTCC dielectric material and a preparation method thereof, wherein the glass powder is composed of 15-16 parts by mass of a first melting point glass powder and 3-5 parts by mass of a second melting point glass powder, wherein the first melting point glass powder is prepared from the following raw materials in parts by mass: 35-45 parts of CaO, 15-20 parts of B2O3, 36-46 parts of SiO2, 0.1-1 parts of K2O, 1-2 parts of Na2O, 0.1-1 parts of La2O3 and 0.1-2 parts of Nd2O3; the second melting point glass powder is prepared from the following raw materials in parts by mass: 35-45 parts of CaO, 33-43 parts of SiO2 and 16-26 parts of B2O3; the present invention selects two rare earth oxides, La2O3 and Nd2O3, to replace part of CaO for co-doping modification of calcium borosilicate glass to obtain excellent LTCC dielectric material with a dielectric constant of 5.6-6.0 and a dielectric loss of (1-40GHz) <0.002, and has excellent dielectric properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a graph showing the relationship between the mass percentage of B2O3 and the volume density of dielectric materials provided in the embodiments and comparative examples of the present invention;

[0027] Figure 2 is a graph showing the relationship between the mass percentage of B2O3 and the shrinkage rate of the dielectric materials provided in the embodiments of the present invention and the comparative examples;

[0028] Figure 3 is a relationship diagram between B2O3 mass percentage and dielectric constant of dielectric materials provided in the embodiments and comparative examples of the present invention;

[0029] Figure 4 Schematic diagram of punching holes in shrinkage detection samples of dielectric materials provided in the embodiments and comparative examples of the present invention;

[0030] Figure 5 Schematic diagram of cutting a sample for shrinkage detection of a dielectric material provided in the embodiments of the present invention and the comparative examples; DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0032] The shrinkage test method used in the present invention comprises the following steps:

[0033] (1) Randomly cut 10 LTCC green ceramic sheets with a size of 130 mm × 130 mm from the green ceramic tape roll;

[0034] (2) Take one of the raw porcelain pieces, such as Figure 4 As shown in the figure, the following three through holes are punched on the raw ceramic sheet:

[0035] ① 4 stacking positioning holes (alignment holes) - the through hole diameter is 3mm, each hole is symmetrically located at the four corners of the raw porcelain sheet, and the center distance between adjacent holes is 122mm;

[0036] ② 16 holes for sintering shrinkage detection - the through hole diameter is 0.3mm, consisting of 4 symmetrically distributed units, with a unit interval of 7mm, 4 holes in each unit, and the center distance between adjacent holes in the unit is 50mm;

[0037] ③ 60 slices are aligned with hole bars - the diameter of the through hole is 0.15mm, and every 5 holes form a straight hole bar in the X or Y direction. The center distance between adjacent holes in the straight hole bar is 0.6mm. There are 3 groups of column hole bars in the X direction and 3 groups of row hole bars in the Y direction. Each group of column hole bars and row hole bars is composed of a pair of 5-hole straight hole bars. The center distance between column hole bars and row hole bars is 57mm and they are symmetrically distributed on the green porcelain piece;

[0038] (3) Another 9 green ceramic sheets, but only the 4 stacking alignment holes described in item (2) (1) are punched, and the holes for sintering shrinkage detection and the slice alignment holes are not punched;

[0039] (4) stacking and vacuum-sealing the 10 raw ceramic sheets punched with holes in (2) and (3), with the raw ceramic sheet punched with holes in (2) placed on the top layer;

[0040] (5) isostatically laminating 10 layers of loose LTCC green ceramic blanks into dense LTCC green ceramic plates at 3000 psi, 70°C, and 10 min;

[0041] (6) Figure 4 The row and column holes in the LTCC raw board are used as slice alignment marks to cut the LTCC raw board into 4 pieces. Figure 5 The unit LTCC green ceramic block with the size of 57mm×57mm shown;

[0042] (7) Use a 3D dimension measuring instrument to measure the center distance A1B1 between holes A and B and the center distance D1C1 between holes D and C on the top green ceramic sheet of each LTCC green ceramic block. Take the average value of the two on the same LTCC green ceramic block as the X-direction center distance of the detection hole of the LTCC green ceramic block before sintering. The corresponding four LTCC green ceramic blocks are recorded as X 11 , X 12 , X 13 , X 14 ;

[0043] (8) Use a 3D dimension measuring instrument to measure the center distance A1D1 between holes A and D and the center distance B1C1 between holes B and C on the top green ceramic sheet of each LTCC green ceramic block. Take the average value of the two on the same LTCC green ceramic block as the Y-axis center distance of the detection hole of the LTCC green ceramic block before sintering. The corresponding four LTCC green ceramic blocks are recorded as Y 11 , Y 12 , Y 13 , Y 14 ;

[0044] (9) Setting the sintering curve according to Table 1, sintering the four LTCC green ceramic blocks into a unit LTCC substrate;

[0045] Table 1

[0046] Initial temperature (℃) Final temperature (℃) Time (min) Rate(℃ / m) 25 450 350~400 1.21~1.06 450 450 100~150 0 450 840 49~97 7.96~4.02 840 851 5~8 2.2~1.38 851 851 15~20 0 851 25 180~270 -4.59~-3.06

[0047] (10) Use a 3D dimension measuring instrument to measure the center distance A2B2 between holes A and B and the center distance D2C2 between holes D and C on the top green ceramic sheet of each LTCC substrate. Take the average value of the two on the same LTCC substrate as the X-direction center distance of the detection hole of the LTCC substrate after sintering. The corresponding four LTCC substrates are denoted as X 21 , X 22 , X 23 , X 24 ;

[0048] (11) Use a 3D dimension measuring instrument to measure the center distance A2D2 between holes A and D and the center distance B2C2 between holes B and C on the top green ceramic sheet of each LTCC substrate. Take the average value of the two on the same LTCC substrate as the Y-axis center distance of the detection hole of the LTCC substrate after sintering. The corresponding four LTCC substrates are denoted as Y21 , Y 22 , Y 23 , Y 24 ;

[0049] (12) According to the formula η Xi = (1-X 2i / X 1i )×100% (where i is 1, 2, 3, and 4, respectively), and the X-direction shrinkage (length direction shrinkage) η of the four LTCC substrates is calculated. X1 , η X2 , η X3 , η X4 ;

[0050] (13) According to the formula η Yi = (1-Y 2i / Y 1i )×100% (where i is 1, 2, 3, and 4, respectively), and the Y-direction shrinkage (width direction shrinkage) η of the four LTCC substrates is calculated. Y1 , η Y2 , η Y3 , η Y4 ;

[0051] (14) The average of the X-axis shrinkage rate and Y-axis shrinkage rate of the four LTCC substrates was taken to obtain the final X-axis shrinkage rate and Y-axis shrinkage rate of the LTCC substrate.

[0052] In the present invention, the preparation of test samples and the dielectric constant and dielectric loss tests are carried out with reference to GB / T 5593-2015 "Structural ceramic materials for electronic components" and GB / T 5597-1999 "Test method for microwave complex dielectric constant of solid dielectrics".

[0053] In the embodiments provided by the present invention, the adhesives used are all polyvinyl butyral (PVB).

[0054] Example 1

[0055] This embodiment provides a millimeter wave low-loss LTCC dielectric material and a preparation method thereof, the preparation method comprising:

[0056] (1) 64 g of CaO, 24 g of B2O3, 66.4 g of SiO2, 1.6 g of K2O, 1.6 g of Na2O, 0.8 g of La2O3, 1.6 g of Nd2O3, 16.2 g of CaO, 8.4 g of B2O3, and 15.4 g of SiO2 were respectively put into a ball mill and ball-milled at 150 rpm for 3 h, taken out and dried to obtain a dried material;

[0057] (2) The dried material is placed in a platinum crucible and melted at 1400°C for 1.5 hours, and then poured into deionized water for quenching to obtain a water-quenched material;

[0058] (3) The water-quenched material was put into the ball mill again and ball-milled at 150 rpm for 3 h, then taken out and sieved through a 600-mesh sieve, and dried to obtain glass powder;

[0059] (4) Take 200 g of the glass powder obtained in step (3), add 40 g of ethanol, 60 g of methyl ethyl ketone and 50 g of a binder and mix well to prepare a slurry;

[0060] (5) The slurry obtained in step (4) is placed in a casting machine for casting treatment at a casting speed of 1 m / min, and is dried in three temperature zones of the casting machine, wherein the drying temperature in the first temperature zone is 45° C., the drying temperature in the second temperature zone is 55° C., and the drying temperature in the third temperature zone is 65° C., thereby preparing a millimeter wave low-loss LTCC dielectric material.

[0061] Example 2

[0062] This embodiment provides a dielectric material and a preparation method thereof. Different from Embodiment 1, in this embodiment, step (1) in the preparation method is: 64 g of CaO, 24 g of B2O3, 66.4 g of SiO2, 1.6 g of K2O, 1.6 g of Na2O, 0.8 g of La2O3 and 1.6 g of Nd2O3 and 16.2 g of CaO, 8.4 g of B2O3 and 15.4 g of SiO2 are respectively put into a ball mill and ball-milled at 150 rpm for 3 h, taken out and dried to obtain a dried material.

[0063] Comparative Example 1

[0064] This comparative example provides a dielectric material and a preparation method thereof. Different from Example 1, in this comparative example, step (1) in the preparation method is: 64 g of CaO, 24 g of B2O3, 66.4 g of SiO2, 1.6 g of K2O, 1.6 g of Na2O, 0.8 g of La2O3 and 1.6 g of Nd2O3 and 16.2 g of CaO, 8.4 g of B2O3 and 15.4 g of SiO2 are respectively put into a ball mill and ball-milled at 150 rpm for 3 hours, taken out and dried to obtain a dried material.

[0065] Comparative Example 2

[0066] This comparative example provides a dielectric material and a preparation method thereof. Different from Example 1, in this comparative example, step (1) in the preparation method is: 64 g of CaO, 24 g of B2O3, 66.4 g of SiO2, 1.6 g of K2O, 1.6 g of Na2O, 0.8 g of La2O3 and 1.6 g of Nd2O3 and 16.2 g of CaO, 8.4 g of B2O3 and 15.4 g of SiO2 are respectively put into a ball mill and ball-milled at 150 rpm for 3 hours, taken out and dried to obtain a dried material.

[0067] It can be calculated that the B2O3 contents of the dielectric materials provided in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are 15wt%, 18wt%, 12wt% and 21wt% respectively.

[0068] The volume density, shrinkage rate and dielectric constant of the dielectric materials provided in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were tested respectively.

[0069] The test results of bulk density are as follows: Figure 1 As shown in the figure, with the increase of B2O3 content, the density of the dielectric material increases first and then slightly decreases, and the shrinkage rate is consistent with the density change trend. When the B2O3 content is 15wt% and 18wt%, the volume density of the sample reaches the maximum value of 2.45g / cm 3 This shows that the sample with this B2O3 content has the highest sintering densification degree and the least number of pores, which is beneficial to reducing the dielectric loss of the dielectric material.

[0070] The shrinkage test results are as follows: Figure 2 As shown in the figure, with the increase of B2O3 content, the shrinkage rate of the dielectric material shows a trend of first increasing and then slightly decreasing. When the B2O3 content is 18wt%, the shrinkage rate of the sample reaches a maximum value of 14.5%.

[0071] Figure 3 The figure shows the dielectric properties test results of four samples with different B2O3 contents. It can be seen from the figure that when the B2O3 content varies between 12% and 21%, the dielectric constant of the sample is between 4.25 and 7.15, and with the increase of B2O3 content, the dielectric constant of the sample shows a trend of first increasing and then decreasing. When the B2O3 content is 18%, the maximum dielectric constant value is 7.15, and the dielectric loss gradually decreases.

[0072] Based on the analysis results of the comprehensive sintering performance and dielectric property tests, it is believed that the formula provided by Example 1, which has the highest degree of densification and excellent dielectric properties and a B2O3 content of 15%, has the best performance.

[0073] Comparative Example 3

[0074] This comparative example provides a dielectric material and a preparation method thereof. Different from Example 1, in this comparative example, step (5) in the preparation method is: taking the slurry prepared in step (4) and placing it into a casting machine for casting treatment, the casting speed is 1m / min, and drying it in three temperature zones of the casting machine, wherein the drying temperature of the first temperature zone is 35°C, the drying temperature of the second temperature zone is 45°C, and the drying temperature of the third temperature zone is 55°C, to prepare the dielectric material.

[0075] Comparative Example 4

[0076] This comparative example provides a dielectric material and a preparation method thereof. Different from Example 1, in this comparative example, step (5) in the preparation method is: taking the slurry obtained in step (4) and placing it into a casting machine for casting treatment, the casting speed is 1m / min, and drying it in three temperature zones of the casting machine, wherein the drying temperature of the first temperature zone is 55°C, the drying temperature of the second temperature zone is 65°C, and the drying temperature of the third temperature zone is 75°C, to prepare the dielectric material.

[0077] The appearances of the dielectric materials provided in Example 1, Comparative Example 3 and Comparative Example 4 were observed respectively, and the results are shown in Table 2.

[0078] Table 2 Appearance of dielectric materials corresponding to different drying temperatures

[0079] Case Comparative Example 3 Example 1 Comparative Example 4 Drying temperature 35℃:45℃:55℃ 45℃:55℃:65℃ 55℃:65℃:75℃ Appearance Not dry, sticky Dry, no cracks Dry but with slight cracks

[0080] From Table 2, it can be seen that when the final stage temperature is set to 55℃, the solvent is not completely dried; on the contrary, when the initial stage temperature is set to 55℃, due to the large temperature difference, the surface of the green porcelain film has been quickly dried to form a film layer, and in the subsequent drying process, the inconsistent shrinkage directly leads to cracks in the green porcelain tape. Therefore, moderate three-stage drying temperatures are conducive to the drying and good appearance of the green porcelain tape after casting, and the reasonable drying temperatures are 45℃:55℃:65℃.

[0081] Comparative Example 5

[0082] This comparative example provides a dielectric material and a preparation method thereof. Different from Example 1, in this comparative example, step (5) in the preparation method is: taking the slurry prepared in step (4) and placing it into a casting machine for casting treatment, the casting speed is 0.6 m / min, and drying it in three temperature zones of the casting machine, wherein the drying temperature of the first temperature zone is 45°C, the drying temperature of the second temperature zone is 55°C, and the drying temperature of the third temperature zone is 65°C, to prepare the dielectric material.

[0083] Comparative Example 6

[0084] This comparative example provides a dielectric material and a preparation method thereof. Different from Example 1, in this comparative example, step (5) in the preparation method is: taking the slurry obtained in step (4) and placing it in a casting machine for casting treatment, the casting speed is 1.4 m / min, and drying it in three temperature zones of the casting machine, wherein the drying temperature of the first temperature zone is 45°C, the drying temperature of the second temperature zone is 55°C, and the drying temperature of the third temperature zone is 65°C, to prepare the dielectric material.

[0085] The appearances of the dielectric materials provided in Example 1, Comparative Example 5 and Comparative Example 6 were observed respectively, and the results are shown in Table 3.

[0086] Table 3 Appearance of medium materials corresponding to different flow rates

[0087] Case Comparative Example 5 Example 1 Comparative Example 6 Flow rate 0.6m / min 1.0m / min 1.4m / min Appearance Dry, many cracks, with a small amount of particles Dry, no cracks Not dry, sticky

[0088] From Table 3, we can see that the appearance of the porcelain belts with a slower flow rate of 0.6 m / min is poor, with more cracks and a small amount of particles. This may be due to the long drying time and exposure time in the air, which is prone to cracks and impurities brought by the air; the flow rate of 1.4 m / min is too fast compared to 1.0 m / min, the green porcelain belt is not in the drying channel for enough time, and the solvent in the slurry is not completely discharged. In summary, it is considered that the flow rate of 1.0 m / min is more appropriate.

[0089] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.

Claims

1. A millimeter wave low-loss LTCC dielectric material, wherein the LTCC is a low temperature co-fired ceramic, characterized in that: The invention is prepared from the following raw materials in parts by weight: 7-9 parts of ethanol, 11-13 parts of methyl ethyl ketone, 38-42 parts of glass powder and 9-11 parts of a binder; The glass powder is composed of 15-16 parts by mass of a first melting point glass powder and 3-5 parts by mass of a second melting point glass powder, wherein the first melting point glass powder is doped with La2O3 and Nd2O3; The first melting point is 1490-1510°C; the second melting point is 1390-1410°C.

2. The millimeter wave low-loss LTCC dielectric material according to claim 1, characterized in that: The first melting point glass powder is prepared from the following raw materials in parts by mass: 35-45 parts of CaO, 15-20 parts of B2O3, 36-46 parts of SiO2, 0.1-1 parts of K2O, 1-2 parts of Na2O, 0.1-1 parts of La2O3 and 0.1-2 parts of Nd2O3.

3. The millimeter wave low-loss LTCC dielectric material according to claim 1, characterized in that: The second melting point glass powder is prepared from the following raw materials in parts by mass: 35-45 parts of CaO, 33-43 parts of SiO2 and 16-26 parts of B2O3.

4. The millimeter wave low-loss LTCC dielectric material according to claim 1, characterized in that: The particle size of the glass powder is 1.8-2.2 μm.

5. A method for preparing a millimeter wave low-loss LTCC dielectric material as claimed in any one of claims 1 to 4, characterized in that: include: Obtaining raw materials of a first melting point glass powder and a second melting point glass powder according to weight, and subjecting them to ball milling, drying, melting and water quenching treatments in sequence to obtain a water-quenched material; The water-quenched material is ball-milled, sieved and dried to obtain glass powder; Obtain the glass powder, ethanol, methyl ethyl ketone and binder according to weight parts, mix the above materials evenly, and prepare slurry; The slurry is subjected to tape casting treatment and dried under multiple temperature conditions to prepare a millimeter wave low-loss LTCC dielectric material.

6. The method for preparing a millimeter wave low-loss LTCC dielectric material according to claim 5, characterized in that: The ball milling time is 2-4 hours, and the rotation speed is 100-200 rpm.

7. The method for preparing a millimeter wave low-loss LTCC dielectric material according to claim 5, characterized in that: The melting temperature is 1300-1500° C. and the melting time is 1-2 hours.

8. The method for preparing a millimeter wave low-loss LTCC dielectric material according to claim 5, characterized in that: The mesh number of the sieving is 600 meshes.

9. The method for preparing a millimeter wave low-loss LTCC dielectric material according to claim 5, characterized in that: The equipment for the casting process adopts a casting machine, and the casting speed is 1.0-1.2 m / min; And / or, the drying under multiple temperature conditions is specifically drying in three temperature zones of the casting machine, wherein the drying temperature in the first temperature zone is 42-48°C, the drying temperature in the second temperature zone is 52-58°C, and the drying temperature in the third temperature zone is 62-68°C.